Grzech Kaina w ocenie Ojców Kościoła - Czyżewski, Bogdan (Vox Patrum, 2015)
Fathers of the Church have left comments on Genesis as well as other works, which explain not only the biblical descriptions of the origins of the world and man, but also Gen 4: 1-16, where it speaks of the sin of Cain. In this paper we present an assessment of the sin of Cain made by some of the Fathers of the Church. It should be noted that they do not stop only on the sin of fratricide, although condemn it the most, but focus their attention also on other sins of Cain, which preceded and led to the killing of Abel by his jealousy, anger, evil thoughts, insincerity. Fathers of the Church recognize the individual and social character of the sins of Cain, which manifests itself in leaving his from God and separation from relatives. This resulted in a permanent division of the family. Fathers also point to the mercy of God and a willingness to forgive. Commentators of Gen 4:1-16 biblical text, however, do not see in Cain repent for any sin committed by him.